Et rids af Grundtvig-forskningen og dens stilling i efterkrigstidens Danmark. William Michelsen in memoriam - Pedersen, Kim Arne (Grundtvig-studier, 2002)
Et rids af Grundtvig-forskningen og dens stilling i efterkrigens Danmark. William Michelsen in memoriam [A sketch o f Grundtvig scholarship and its position in postwar Denmark. In memory of William Michelsen]By Kim Arne Pedersen With the death of William Michelsen a distinct era in the history of Gr scholarship reached its close, for he was the last surviving member of the small circle who (gathered in Bishop C. I. Scharling’s residence in Ribe for Gr’s birthday ) celebrated on the stroke of midnight the founding of The Grundtvig Society of 8th September 1947 [Grundtvig-Selskabet af 8. September 1947] which was to prove such an important initiative in Danish academic activity and in Danish culture more widely. In the forthcoming reinstatement of Gr in the mainstream of Danish scholarship and debate Michelsen was to maintain a long, unstinting and untiring involvement, both through his own scholarly output and through the encouragement, advice and criticism he offered to younger and rising scholars.Michelsen was markedly the product of his own background in a middleclass family linked over two generations with teaching, a liberal theological outlook and a quiet Christian piety in the home. Similarly, the motives and objectives of his involvement with Gr over his long working-life were distinctly responsive to the times through which he lived, and not least to the threats posed to democracy in the twentieth century by totalitarian regimes.Like others of his distinguished contemporaries, notably his lifelong friend Henning Høirup, he perceived Gr as »our contemporary« whose life-work remained of living relevance and should be accorded a functional place within the national cultural inheritance.Though not a theologian by formal education, Michelsen along with his generation came to be influenced by Karl Barth’s insistence that the revealed word of God must be the premise of any confession. This principle inspired his own studies of Gr’s thought-world, and particularly of Gr’s thesis of history, which in turn led him to see that religious idealism alone was not a sufficient response to the actualities of living in the present moment. Here he was also fairly clearly influenced by Hal Koch who, during the years of the German occupation of Denmark in the Second World War, was most instrumental in presenting Gr as his generation’s contemporary.With fellow-scholars such as Høirup and Regin Prenter, Michelsen found Gr’s authorship informed not only by Christianity’s radical profession of the forgiveness of sins but also, equally importantly, of a creation-theology which for them made it possible to harmonise the modem world’s scientific awareness with a belief that life and the universe were created by God. His contribution to the anthology Grundtvig og grundtvigianismen i nyt lys [Gr and grundtvigianism in a new light] (1983) is a key discussion of Gr’s conversion in 1810 and Gr’s relationship to Søren Kierkegaard. Various of Michelsen’s writings set forth Gr’s historical perspective as being based upon a mosaicchristian view, in a consciousness of Gr’s shift from faith to knowledge, from church to school around the critical year 1832. The view that he and Kai Thaning constitute opposite poles misrepresents the affinities and distinctions carefully drawn by Michelsen himself (‘ Brev til en Grundtvigforsker’ [Letter to a Gr-scholar] in Dansk Udsyn 1964,443); nevertheless, his analysis of Gr’s universal-historical work formulates a significant challenge to Thaning’s reading of Gr and demonstrates the sense in which Gr was, as Michelsen later wrote in Grundtvig Studier 1983, ‘ Sin samtids kritiker’ [Critic of his own times].After early work on H. C. Ørsted, Michelsen wrote his doctoral thesis, published as Tilblivelsen af Grundtvigs historiesyn [The formulation of Gr’s view of history] (Copenhagen, 1954). During this period (1941) he married Signe, niece of the Greenland explorer Knud Rasmussen who was herself an authority on Greenland and collaborated in translating Gr into the Greenlandic language. His doctoral thesis was based on an examination of the works Gr is known to have studied in his formative years (though he has been criticised for exaggerating the cohesion of the sources of influence upon Gr) out of which Gr shaped a view of history which was not a learned construct or theory but a conscious expression of the picture he formed for himself of existence.Michelsen depicts Gr as standing in opposition to the contemporary compromise between Christianity and romanticism, and as allowing the biblical perspective of history to model his own exposition of history.Characteristically, when his doctoral thesis was eventually overshadowed by the work of Sigurd Aa. Aames (1961) with its different approach, methodology and findings, Michelsen responded constructively (Grundtvig Studier 1962). Meanwhile he had been extending his own exploration of the way in which Gr’s Christian view of history developed after 1810, in Den sælsomme forvandling i N. F. S. Grundtvigs liv [The strange Metamorphosis inNFSG’slife] (1956). His two studies together raised issues-concerning for example Gr’s relationship to Lutheran tradition, his view of the divine image in man, and affinities between Gr and Kiekegaard’s existential standpoint - which ought to have generated a greater scholarly response than has been the case.Many of Michelsen’s articles in Grundtvig Studier remain indispensable items for students and researchers. He made a distinguished contribution to the great catalogue of the Grundtvig archives in the Royal Library, Copenhagen. Much work (in which his son Knud collaborated) on the transcription of unprinted Gr manuscripts and the identification of textual correlations illustrative of Gr’s philosophical thinking remains unpublished - though the big two-part introduction to Gr’s thought as reflected in his Danne-Virke (Grundtvig Studier 1985-86) to some extent compensates for this. Michelsen’s appointment (1968) to a lectureship in Aarhus University, in fulfilment of Professor Gustav Albeck’s desire to give Gr a central place in Danish studies, coincided with turbulent times which he did not find easy, but the fruits of his teaching are seen in the long series of fine articles by his pupils in Grundtvig Studies, of which he became an editor in 1969, scrupulously active to the last. In 1997 he was honoured by the Grundtvig-Selskab upon its Fiftieth Anniversary. He was an active participant in the newly-founded Grundtvig Academy in Vartov, in 2000.With William Michelsen’s death a notable Christian humanist and scholar has passed on. May his memory be held in honour.